Editorial (Thematic Issue: Cardiovascular Drug Therapy in Paediatric Age: From Metabolomics to Clinical Practice) - Paolo Bassareo, Pier; Fanos, Vassilios (Current Medicinal Chemistry, 2014)
In adult patients, cardiovascular drugs are widely administered in the treatment of numerous diseases. The indications and doses are strictly codified by international Guidelines, which are periodically updated by the American and European Societies of Cardiology. In paediatric patients, however, the situation is substantially different. The lack of large interventional studies on the use of these compounds has led to a greater uncertainty, with a less extensive administration and more limited indications. Furthermore, some important differences in therapeutic approach for the same diseases are present between the U.S. and Europe. The purpose of this Special Issue is to review the pharmacological treatment of certain heart diseases, such as heart failure, and arterial blood pressure, which can result in both adult and pediatric patients [1, 2]. Differences and similarities have been highlighted. Regarding the differences in medical treatment for the same disease in the U.S. and Europe, it has been emphasized that the regulation of drugs is largely determined not only by scientific considerations, but also by other concerns – legal, cultural - which vary in different parts of the world. Such discrepancies are found even in the informational documents provided by pharmaceutical companies (different in USA and Europe for the same drug) and drug agencies (different between FDA and equivalent agencies in Europe). In this issue of Current Medicinal Chemistry, a specific paper is dedicated to the pharmacological treatment of the patency of ductus arteriosus in neonates, which is still a controversial issue. In fact, notwithstanding ibuprofen appears to be lesser dangerous for newborns than indomethacin, with a similar efficacy in closing the ductus; in a number of countries the latter is still administered to all preterm subjects as a prophylactic tool [3]. An unusual case report is the interesting starting point to perform an extensive literature review about the new indications of beta blockers [4]. In this respect, beta blockers, most specifically propranolol, have serendipitously been shown to induce involution of infantile hemangiomas. Mechanisms of action, target doses, formulation, contraindications and cardiovascular monitoring for beta blockers have been analyzed as well. It has recently been demonstrated that preterm birth is negatively associated with an early onset of cardiovascular diseases. Cardiovascular mortality is higher among former preterm adults than those born at term. This condition is referred to as cardiovascular perinatal programming. Metabolomics, a new and promising technique which allows the systematic study of the complete set of metabolites in a biological sample, has been recently applied to the identification of a possible future cardiovascular system involvement in subjects born preterm. Based on these premises, the purpose of the last review was to analyse the relationship between impaired growth during intrauterine life and adult cardiovascular disease risk and death [5].